2018
DOI: 10.1038/s41536-018-0061-4
|View full text |Cite
|
Sign up to set email alerts
|

Sustained release of decorin to the surface of the eye enables scarless corneal regeneration

Abstract: Disorganization of the transparent collagenous matrix in the cornea, as a consequence of a variety of infections and inflammatory conditions, leads to corneal opacity and sight-loss. Such corneal opacities are a leading cause of blindness, according to the WHO. Public health programs target prevention of corneal scarring, but the only curative treatment of established scarring is through transplantation. Although attempts to minimize corneal scarring through aggressive control of infection and inflammation are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 57 publications
(47 reference statements)
0
37
0
Order By: Relevance
“…56 Decorin formulation has shown promising outcomes in the murine model showing reduced corneal opacity with antiscarring properties in patients with microbial keratitis. 57 The finding that decorin is lowered in Tenon's fibroblast and AH before surgery opens avenues for investigating decorin as a biomarker or as a therapeutic target to enhance its levels in patients undergoing trabeculectomy.…”
Section: Discussionmentioning
confidence: 99%
“…56 Decorin formulation has shown promising outcomes in the murine model showing reduced corneal opacity with antiscarring properties in patients with microbial keratitis. 57 The finding that decorin is lowered in Tenon's fibroblast and AH before surgery opens avenues for investigating decorin as a biomarker or as a therapeutic target to enhance its levels in patients undergoing trabeculectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Hindman et al and Kim et al [38,39] reported that PA decreased the number of myofibroblast in damaged cornea, but this reducing effect disappeared when PA treatment is discontinued. In addition, Hill et al [40] reported that corticosteroid is ineffective to eliminate myofibroblast population in damaged cornea. Thus, PA seems to improve corneal haze regardless of depletion of myofibroblast population (Figure 1 and Supplementary Figure S1).…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative results showed that rabbits treated with decorin had significantly less ECM deposition 14 days after surgery, as well as suppressed conjunctivital scarification. Hill et al (2018) designed gellan based fluid gels for sustained delivery of human recombinant decorin through eye drops for corneal regeneration and found improved ocular function. Due to its ability to delay collagen fibrillogenesis, decorin is an attractive therapeutic candidate for anti-scarring treatments.…”
Section: Decorinmentioning
confidence: 99%
“…Dermatan sulfate Macular degeneration, diabetic retinopathy, diabetic macular edema (Devore et al, 2010) Corneal wound healing (Grisanti et al, 2005;Hill et al, 2018) Anti-scarring (Stuart et al, 2011;Ahmed et al, 2014;Wang et al, 2016) Oncosupression (Yang et al, 2015;Wang et al, 2016;Liu et al, 2017;Oh et al, 2017a) Abdominal aortic aneurysm (Shen et al, 2017) Vascular neointimal hyperplasia (Paderi et al, 2011;Scott and Panitch, 2014;Scott et al, 2017) Lumican Keratan sulfate Corneal wound healing (Chakravarti, 2002;Gesteira et al, 2017) Bacterial lung infections (Shao et al, 2012;Shao et al, 2013a) Scarring (Yeh et al, 2005;Liu et al, 2013;Yamanaka et al, 2013;Zhao et al, 2016) Melanoma (Zeltz et al, 2009;Pietraszek et al, 2013)…”
Section: Decorinmentioning
confidence: 99%